Major predictors of bruxism in pediatric dentistry: a systematic review - Garcia, Guilherme Augusto Lima (MedNEXT Journal of Medical and Health Sciences, 2025)
Introduction: There is difficulty in determining the prevalence of the habit of bruxism and therefore are important evaluation method, since only 5-20 % of the carrier population of habit are aware that perform the habit. Objective: This study aimed to conduct a quantitative and qualitative overview of the literature findings on the treatment of bruxism in pediatric dentistry. Methods: The PRISMA Platform systematic review rules were followed. The search was carried out from November 2024 to January 2025 in the Scopus, PubMed, Science Direct, Scielo, and Google Scholar databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results and Conclusion: 112 articles were found, 42 articles were evaluated in full and 33 were included and developed in the present systematic review study. Considering the Cochrane tool for risk of bias, the overall assessment resulted in 20 studies with a high risk of bias and 32 studies that did not meet GRADE. Most studies did not show homogeneity in their results, with X2=94.8%>50%. Some authors concluded that in children, there are several etiological factors of bruxism, such as psychological, local factors, occupational activities, and systemic conditions, factors such as stress and anxiety little considered the influence of allergic phenomena in this dysfunction. According to the author, in the allergic factor, nocturnal bruxism is from a reflex initiated by the increase in negative pressure in the tympanic cavities when there are successive allergic edemas in the mucosa in the Eustachian tubes. It is concluded that there are a large number of jobs in pediatric dentistry using muscle relaxant boards as a treatment for bruxism and temporomandibular disorder and according to the results obtained with a critical significance level, the vast majority of authors have confirmed the benefits of using the plates. It was concluded that bruxism has a multifactorial etiology because there is ample evidence that emotional stress is a major trigger, while occlusal interference is a predisposing factor. But some theories admit that occlusal disharmony is as etiological factor of bruxism.